New Method of Materials Flow Calculation for Double-String SLCI Type Cement Plant (Part 1: The Whole Clinker Plant) - Prihadi Setyo Darmanto; Izzan Hakim Muzakki; I Made Astina; Firman Bagja Juangsa; Alfi Amalia; Arief Syahlan (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Materials flow values are instrumental in many industries for controlling and simulating processes, designing new equipment as well as modifying existing plants. They are sometimes impossible to determine by direct measurement in an operating plant due to the very high temperatures. This study attempted to overcome the difficulties associated with this measurement by proposing a new method to calculate materials flow of a double-string suspension preheater type of cement plant with separate line and in-line calciners (SLC-I), with heat balance error less than 1%. This study was divided into two sequential parts, with the first part presented in this paper. The methodology of the first part was to solve the conservation law of the main clinker plant equipment, supported by Bogue’s equation, the heat of calcination, and the thermodynamic properties of the related materials. The least-square method was employed for solving the overdetermined system equations obtained in the second part. The results of the first part were: the ratio of heat formation to specific heat consumption was 52.13% (> 50%), and the gas exhausted from the plant yielded more than 117 MW heat equivalent, which can potentially be recovered for electricity production.